To the Frame of a Tableau of a School (Training and Practice : Journal of Educational Sciences, 2012)
In a district primary school not only the children say farewell during the leaving ceremony of this year but a chapter ends in the life of the school too. The special education in this school goes back to 20 years. Teachers spent extra work hours with the initiation of renewal the teachers created this school for helping parents and pupils. If it is about the realisation of integration then the parting is joyful. Is it true? This essay tries to give you the answer.